A current source inverter with series connected AC capacitors for photovoltaic application with grid fault ride through capability - Photong, Chonlatee; Klumpner, Christian; Wheeler, Patrick (2009)
The current source inverter (CSI) is preferred to interface a renewable source such photovoltaics (PV) to the AC power grid because it can provide smooth current source in the DC side, which fits to the PV behaviour and also steps-up the voltage from DC side to AC side, which allows smaller and safer DC voltage levels to be used. However, the CSI has the problem that during an AC grid fault, it cannot operate properly. In this paper, a single-stage power conversion approach based on a CSI inverter with series capacitors is proposed, proven to provide improved efficiency and smaller DC inductor size and the capability to ride through AC grid faults with full reactive power injection support when compared to a standard CSI.